Implementasi Metode MOORA Dalam Sistem Pendukung Pemilihan Kepala Mandor Pada PT. PP Proyek Bendungan Lau Simeme - Fresillya Br Sembiring; Nelly Astuti Hasibuan; Bister Purba (STMIK Budi Darma, 2022)
The head foreman is someone who works in the construction field who will have expertise in leading several jobs at a particular company when working on a project he is responsible for all activities in the field of work. The existence of the foreman is very helpful for other employees in carrying out the tasks that must be done in order to achieve company goals. Problems that often occur during the selection of the head foreman at PT. The PP of the Lau Simeme Dam Project is still subjective and does not match the position so that PT. The PP of the Lau Simeme Dam Project has not increased and is not being driven forward, of course it will have an impact on other operations. This is certainly not very good because it affects the smooth operation of PT. The PP Lau Simeme Dam Project and the objectives are not correct. Therefore we need a decision support system to uphold objectivity in the process of selecting the chief foreman. In a decision support system, the MOORA method can be applied which is able to produce the best decision and several alternatives are inputted. To overcome the selection of the head foreman, the method used is the implementation of the MOORA method. This method can filter the best alternatives because the MOORA method is able to determine goals based on conflicting criteria, so the use of this method is appropriate to solve this problem.